Weak exogeneity in the financial point processes - Yongdeng Xu (Cardiff University, Cardiff Business School, 2013)
This paper analyses issues related to weak exogeneity in a financial point process. We extend the Hausman test of weak exogeneity in a time series model and propose three cases in which weak exogeneity conditions will break down. The simulation study suggested that a failure of the exogeneity assumption implied biased estimators. The bias is very large in the third case non-weak exogeneity, which makes the econometric inferences on the parameters unreliable or even misleading. We then derive an LM test for weak exogeneity. The LM test is attractive because it only requires estimation of the restricted model. The empirical results indicate that the weak exogneity of duration is often rejected for frequently traded stocks, but is less likely to be rejected for infrequently traded stocks.
Keywords: 330; weak exogeneity; ACD model; LM test; point process; market microstructure